Kebijakan Fiskal dan Moneter dalam Perspektif Ekonomi Islam: Kerangka Kebijakan untuk Kestabilan dan Keadilan Ekonomi - Mohammad Habibi; Tiara; Anis Wulandari; Intan (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
This article discusses fiscal and monetary policy from the perspective of Islamic economics, which is based on the principles of justice and sustainability. The purpose of this study is to conceptually describe the framework of fiscal and monetary policy in the Islamic economic system and to recommend policy directions that are in line with sharia principles. This study employs a qualitative-descriptive method using library research. Data were collected from relevant primary and secondary literature. The results of the study indicate that Islamic fiscal policy prioritizes zakat, sharia taxes, and public spending for wealth distribution, while Islamic monetary policy rejects usury and prioritizes exchange rate stability and strengthening the real sector through sharia financing. This study contributes theoretically to the development of the Islamic economic system and offers alternative policies that can be applied in national and global financial systems.